1991
DOI: 10.1159/000107171
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Intrathecal Synthesis of Immunoglobulin G in Primary Degenerative Dementia (Alzheimer's Disease)

Abstract: Serum and cerebrospinal fluid (CSF) from 118 patients with primary degenerative dementia (PDD; Alzheimer''s disease) and 50 healthy controls were examined in order to investigate intrathecal synthesis of immunoglobulin G (IgG), defined as an elevated IgG index (≧ 0.7) and/or the presence of oligoclonal IgG bands in CSF but not in serum. In the PDD group, 7 patients (6%) showed an intrathecal IgG synthesis. Eight patients (7%) showed oligoclonal IgG bands in serum and CSF, interpreted as a diffusion of IgG acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Recent findings in the aged rodent brain also support an aging-dependent increase of BBB permeability, which may show regional differences (Bake et al, 2009 ; Blau et al, 2012 ; Lee et al, 2012 ). However, other studies in humans have suggested that BBB alterations are very subtle throughout adult life, or could even be related to subclinical disease (see, for example, Blennow et al, 1991 ; Garton et al, 1991 ; Skoog et al, 1998 ) and thus spare the non-diseased brain.…”
Section: T Cells In the Healthy Aged Brainmentioning
confidence: 99%
“…Recent findings in the aged rodent brain also support an aging-dependent increase of BBB permeability, which may show regional differences (Bake et al, 2009 ; Blau et al, 2012 ; Lee et al, 2012 ). However, other studies in humans have suggested that BBB alterations are very subtle throughout adult life, or could even be related to subclinical disease (see, for example, Blennow et al, 1991 ; Garton et al, 1991 ; Skoog et al, 1998 ) and thus spare the non-diseased brain.…”
Section: T Cells In the Healthy Aged Brainmentioning
confidence: 99%